2007
DOI: 10.1021/la7009868
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Adsorption and Desorption of CO2 on Cu/ZrO2 and ZrO2 Catalysts

Abstract: The interaction between carbon dioxide and two zirconia catalysts-a Cu/ZrO2 catalyst containing 34% copper and a pure ZrO2 catalyst-was studied by pulse adsorption and temperature-programmed desorption methods. Kinetic modeling by nonlinear regression was applied to acquire information on the adsorption and desorption of CO2 relevant in the synthesis of methanol from carbon dioxide. A model that included three types of adsorption sites described well the experimental data for both Cu/ZrO2 and ZrO2. The model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
4
15
0
1
Order By: Relevance
“…Compared with pure zirconia, doping other metal ions into zirconia will change the oxygen vacancy concentration and acidity and alkalinity of the catalyst surface. [20][21][22] Tomishige et al 23 found that the catalytic activity of ZrO 2 catalyst for the synthesis of DMC is signicantly improved compared with pure ZrO 2 , which is related to the oxygen vacancies generated by the introduction of Ce 4+ . However, the internal effect of OVs on the catalytic reaction is still elusive, which hinders the rational design of catalyst defects.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with pure zirconia, doping other metal ions into zirconia will change the oxygen vacancy concentration and acidity and alkalinity of the catalyst surface. [20][21][22] Tomishige et al 23 found that the catalytic activity of ZrO 2 catalyst for the synthesis of DMC is signicantly improved compared with pure ZrO 2 , which is related to the oxygen vacancies generated by the introduction of Ce 4+ . However, the internal effect of OVs on the catalytic reaction is still elusive, which hinders the rational design of catalyst defects.…”
Section: Introductionmentioning
confidence: 99%
“…16 The carbon-containing species desorb from the surface as CO and CO 2 , usually as such 13 or accompanied by hydrogen or water 17,18 originating from the surface hydroxyl species in the bicarbonates and formates. A few temperature-programmed studies 15,17,19 carried out in a wide temperature range show remarkably complex features for both CO and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high calcination temperature it can be assumed that all carbon sources initially present on the surface have been removed and it seems reasonable to assume that the remaining carbon is re-adsorbed CO 2 and therefore inorganic carbon from air. [64][65][66] A 3, open symbols). An isoelectric point (IEP) between pH 6.8-7.3 can be determined but no apparent correlation between the IEP and the TC can be found.…”
Section: Accepted Manuscriptmentioning
confidence: 99%